METHODOLOGY FOR THE DEVELOPMENT OF LOGICAL REASONING IN PRIMARY SCHOOL PUPILS - Sayfiddinova, Jamila (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2023)
This article is devoted to methodological recommendations on the formation of the logical reasoning skills of primary school students in the process of literary education. On the basis of problematic questions and tasks in the development of logical and creative thinking skills of younger students, it is possible to formulate the logical reasoning skills of students. The article presents the importance of using the heuristic and conversational method, one of the modern technologies for improving the vocabulary of students, the development of a culture of speech, their formation as a comprehensively spiritual harmonious personality and the successful formation of logical thinking skills in young adults.